Increasing Student's Learning Interest In Social Science Learning Through A Cooperative Approach Of Jigsaw Engineering Fourth Class Elementary School 2 Sepunggur - Tanah Bumbu - Akhmad Salbi (CV. Inara, 2021)
This study formulates the problem of whether the cooperative Jigsaw technique can improve teacher skills, student interest in learning, and learning outcomes for fourth grade students at SDN 2 Sepunggur, Tanah Bumbu Regency. This study aims to improve teacher skills, student interest in learning, and student learning outcomes at SDN 2 Sepunggur in applying the Jigsaw type cooperative learning model. The results of the research in the first cycle showed the average percentage of teacher activity in the first cycle was 67.5%, the second cycle was 82.5%, and the third cycle was 92.5%. In addition to teacher activity, student activity in groups also increased, in the first cycle the percentage of student activity was 60%, the second cycle increased 74%, and the third cycle reached 86%. Social Sciences learning outcomes at the beginning of the first cycle obtained the pre-test results of 60.6 and the average post-test score of 69 with classical completeness of 60%. In the second cycle there was an increase with an average value of 77 with classical learning completeness of 76.7%. In the third cycle, learning outcomes increased with an average value of 86.1 with 96.7% learning completeness. This means that at the end of the third cycle, the classical learning mastery has shown according to the success indicators. The results of this study can be concluded, that by using the Jigsaw technique cooperative method can increase teacher activity in managing learning, student activities and student interest in learning which is getting higher. The method also needs to be developed in other subjects, not only applied to Social Sciences subjects, so that it is more varied.